A review of late intraocular lens opacifications. Issue 1 (January 2021) - Kanclerz, Piotr; Yildirim, Timur M.; Khoramnia, Ramin
Abstract : Purpose of review: Phacoemulsification cataract surgery is one of the most commonly performed surgical procedure worldwide. In the majority of cases, intraocular lenses (IOLs) are implanted. Due to the increasing life expectancy and the fact that cataract surgery is performed in earlier stages, the anticipated IOL duration in the eye has increased over the last decades. The aim of this study was to review the types and describe the characteristics of late intraocular lens opacifications. Recent findings: Calcification was the most commonly reported type of opacification in hydrophilic IOLs; it usually negatively impacted the visual function and required IOL explantation. Glistening manifested in hydrophobic acrylic lenses and was frequent in some IOL models. In most cases glistening and subsurface nanoglistenigs do not lead to a decline in visual acuity or require IOL exchange. Current studies indicate that fluid-related phenomena may induce straylight, leading to a decrease of comfort and quality of vision. Summary: Several reports on late IOL opacifications have been published in recent years. In some cases, particularly in glistening, the development of the opacifications might be related to IOL aging. The influence of the fluid-related microvacuoles on the quality of vision requires further research.